Natural Compounds as Oral Remedies for the Treatment of Oral Diseases: A Narrative Review - Swetha Mathiyazhagan; Vinitha Packirisamy (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: The aim of this narrative review is to inform the key role of natural products in the prevention and treatment of common oral diseases such as dental caries‚ gingivitis‚ periodontitis‚ oral candidiasis and oral cancer with the underlying mechanisms. Method: Reporting of this narrative review followed the Scale for the Assessment of Narrative Review Articles (SANRA) guideline․ Review of the literature was conducted on PubMed‚ PubMed Central (PMC)‚ Scopus‚ Web of Science and Google Scholar․ The search period extended from January 2017 to June 2026․ Eligibility criteria: English-language peer-reviewed articles studying natural compounds or phytochemicals that have experimental or clinical evidence in the prevention or treatment of oral diseases․ Exclusion criteria included articles that did not provide biological outcomes or mechanisms‚ or that were not specific to oral diseases․ Out of 800 records‚ 167 duplicates were removed based on the title, year of publication, author names and DOI and 43 studies were included in the qualitative synthesis after screening of titles/abstracts and full texts. Results: Natural compounds have been widely used against oral diseases through the inhibition of microbial growth and biofilm formation‚ inhibition of inflammatory mediators, reduction of oxidative stress via the Nrf2 pathway activation‚ wound healing/epithelial proliferation‚ antifungal effects against oral Candida spp‚ and apoptosis of oral cancer cells via modulation of the Bax/Bcl-2‚ caspases‚ PI3K-Akt‚ and VEGF signaling pathways․ Nanocarriers such as nanoparticles‚ nanogels‚ hydrogels‚ liposomes‚ and mucoadhesive formulations improved the bioavailability and pharmacological activities of these six bioactive compounds․ Conclusions: Multi-targeted natural products may act as a potential therapeutic approach to treating and preventing oral diseases by inducing strong anti-microbial‚ anti-inflammatory‚ anti-oxidative‚ anti-fungal‚ and anti-cancer effects․ However‚ further experimental evidence is needed to formulate products with standardized delivery systems‚ pharmacokinetic studies‚ and well-designed clinical trials prior to the development of products with clinical use․